Maximising Restitution Penalties as a System of Fines and Compensation in Human Trafficking Judgements - Rina Melati Sitompul; Elwi Danil; Mahmud Mulyadi; Mohammad Ekaputra; Rosmalinda Rosmalinda (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Restitution for victims of human trafficking has become a fundamental aspect of criminal compensation within the criminal procedure system. While compensation is crucial in aiding victims' recovery, its implementation remains suboptimal. In practice, fines intended for victims often end up being paid to the state rather than serving their original compensatory purpose. This research aims to examine the challenges in fulfilling restitution rights and propose an effective legal framework to ensure that compensation reaches victims as intended. This research employs a normative legal research method, utilizing a legislative synchronization approach and a case-based analysis. The findings indicate that offenders frequently evade their responsibility to pay fines, opting for imprisonment as an alternative sanction. This situation highlights the need to reassess the role of fines and restitution in the penal system to ensure victims' rights are upheld. To enhance the effectiveness of restitution as a penal mechanism, this research recommends the establishment of a standardized victim compensation system. A strategic approach is necessary, incorporating asset tracing and restorative justice principles to enforce offenders’ financial obligations. Law enforcement officers, particularly prosecutors, should adopt a dual strategy of coercion and negotiation to ensure compliance. By implementing asset verification and structured settlements, offenders can be encouraged to fulfill their obligations, thereby fostering a legal system that is balanced, efficient, and victim-centered.